Elaboration of fermented dairy beverages: acceptability and viability of probiotic cultures - Adriana Carla Santos de Menezes Ramos; Tânia Lúcia Montenegro Stamford; Erilane Castro Lima Machado; Flávia Rodrigues Bezerra de Lima; Estefânia Fernandes Garcia; Estefânia Fernandes Garcia; Samara Alvachian Cardoso Andrade; Celiane Gomes Maia da Silva (Semina: Ciências Agrárias, 2013)
This work aims to develop formulations of fermented dairy beverages with probiotic cultures (Lactobacillus acidophilus, Streptococcus thermophilus e Bifidobacterium bifidum) yellow monbin flavored, to characterize the chemical composition and to evaluate the stability during refrigerated storage for 28 days.The dairy beverages were developed from an experimental design 3x3, with two factors and three levels each: yellow monbin pulp (15, 20 and 25%) and whey (20, 30 and 40%). Nine formulations were produced and submitted to a sensory acceptability test. Thereafter three selected formulations were evaluated based on their microbiological characteristics, proximate composition, pH and titratable acidity. As the acceptance was higher than 70% in all the formulations, were selected that had a higher proportion of whey. Thus, the formulations F3, F6 e F9 were selected. Considering the proximate composition, the selected formulations not differed regarding for carbohydrates. The dairy beverages showed stability with respect to pH and acidity during the shelf life of 28 days and satisfactory results as the investigation of pathogenic microorganisms within the standards established. Quantification of lactic acid bacteria evidenced high numbers to Lactobacillus acidophilus and Streptococcus thermophilus, values between 11.6 to 10.2 CFU log/mL and 8.9 to 11 CFU log/mL, respectively. The species Bifidobacterium bifidum presented less than 6 log/ mL CFU for the formulations. Based on these results, the selected dairy beverages formulations had nutrition, technology and sensorial feasibility.